Important constraints on soil organic carbon formation efficiency in subtropical and tropical grasslands. (29th July 2021) - Mitchell, Elaine; Scheer, Clemens; Rowlings, David; Cotrufo, Francesca; Conant, Richard T.; Grace, Peter
Abstract: More than 10% of Australia's 49 M ha of grassland is considered degraded, prompting widespread interest in the management of these ecosystems to increase soil carbon (C) sequestration—with an emphasis on long‐lived C storage. We know that management practices that increase plant biomass also increase C inputs to the soil, but we lack a quantitative understanding of the fate of soil C inputs into different soil organic carbon (SOC) fractions that have fundamentally different formation pathways and persistence in the soil. Our understanding of the factors that constrain SOC formation in these fractions is also limited, particularly within tropical climates. We used isotopically labelled residue ( 13 C) to determine the fate of residue C inputs into short‐lived particulate organic matter (POM) and more persistent mineral‐associated organic matter (MAOM) across a broad climatic gradient (ΔMAT 10°C) with varying soil properties. Climate was the primary driver of aboveground residue mass loss which corresponded to higher residue‐derived POM formation. In contrast, MAOM formation efficiency was constrained by soil properties. The differential controls on POM and MAOM formation highlight that a targeted approach to grassland restoration is required; we must identify priority regions for improved grazing management in soils that have a relatively high silt+clay content and cation exchange capacity, with a low C saturation in the silt+clay fraction to deliver long‐term SOC sequestration. Abstract : We know that management practices that increase plant biomass also increase C inputs to the soil, but we lack a quantitative understanding of the fate of soil C inputs into different soil organic carbon (SOC) fractions that have fundamentally different formation pathways and persistence in the soil. This study used isotopically labelled ( 13 C residues) across a broad climatic gradient with varying soil properties to demonstrate that climate was the dominant driver of litter C mass loss and particulate organic matter formation (labile SOC), but mineral‐associated organic matter accumulation (stable SOC) was constrained by soil physical properties.